Inkluzivni judo in etika vključevanja športnikov s posebnimi potrebami v običajne športne sredine - Pečnikar Oblak, Viktorija (Šport (Ljubljana), 2018)
The inclusion of athletes with special needs is promoted at many levels. At the declarative level, it is justified in the slogan "Sport for All", in a document from the European Commission called White Paper on Sport, in the National Sport Program 2014-2023, in the Disabled Action Program 2014-20121 and the like. In practice, we find only a few sports clubs that involve athletes with special needs. The inclusive judo in Slovenia has been in operation for over twenty years and is an example of good practice of "Judo for All". The ethics of martial arts is based on the notion of respect and therefore represents a stimulating environment for inclusion. In the article, we clarify the concept of inclusion in sport. We also provide guidelines for the development of inclusion based on previous experience in the Slovenian judo.
Keywords: borilni športi; etika; inkluzija; inkluzivni judo; judo; sposobnosti; šport za vse; športni klubi; športniki s posebnimi potrebami